ON THE INTEGRAL TRANSFORM SHEHU FOR NONLINEAR FRACTIONAL PROBLEMS - Cetinkaya, Suleyman; Demir, Ali (Matematichki Bilten, 2022)
The intention of this research is to establish the truncated solutions of nonlinear fractional problems, including fractional partial differential equations (FPDEs), by employing the Shehu integral transform first and the iterative method later. The numerical solutions reveal the effectiveness and accuracy of the technique.